The marksman [videorecording (Blu-Ray)] - Lorenz, Robert (Robert B.); Neeson, Liam; Winnick, Katheryn; Raba, Juan Pablo, 1977-; Ruiz, Teresa, 1988- (Universal Pictures Home Entertainment, 2021)
Jim is a former Marine who lives a solitary life as a rancher along the Arizona-Mexican border. But his peaceful existence soon comes crashing down when he tries to protect a boy on the run from members of a vicious cartel.